VEEP. The complete sixth season [videorecording (DVD)] - Mandel, David, 1971-; Zisk, Craig; Louis-Dreyfus, Julia; Chlumsky, Anna; Hale, Tony (Warner Bros. Entertainment, 2017)
Satirical mockumentary following the comedic mishaps of fictional U.S. Vice-President Selina Meyer and her support staff.